A study on the street food dimensions and its effects on consumer attitude and behavioural intentions. Issue 3 (30th May 2018) - Gupta, Vikas; Khanna, Kavita; Gupta, Raj Kumar
Abstract : Purpose: This study aims to find out various dimensions of the risk and benefit perceptions of the consumers of street food vendors. It will identify the reasons which affect consumer's attitude and consumption patterns towards street foods, which bring about changes in their behavioural intentions (repurchase intention and word of mouth intention). Design/methodology/approach: Five risk and two benefit factors were tested on a factor model by exploratory factor analysis using 26 constructs. Two-step approach was followed in which measurement model, having six constructs with 17 measurement items, were assessed, followed by the structural model. This study explained that the consumer attitude is affected by perceived risks and benefits. Further, the risk perception negatively affects the behavioural intentions. A conceptual model was framed to depict the relationships among variables and was empirically tested. Findings: The results indicate that risk and benefit perception of consumers are not only inter-related but also responsible for their changes in attitudes towards the street foods. In the factorial analysis, it was found that perceived benefit factors, i.e. convenience and value, are responsible for positively influencing the attitude of consumers towards street food. The findings indicate that reducing risk perception and increasing benefit perception will positively change the patron's attitude. Originality/value: The data collection was done through a structured questionnaire specifically drafted to collect the relevant data for the study from the 658 street food consumers in Delhi. To examine the factorability of 26 items of risk/benefit perception, 586 observations were used.